The history of noise [on the 100th anniversary of its birth]. - Cohen, L.
In this paper, the author conveys some of the vibrant history of noise that has been involved in the solution of some of the greatest scientific, mathematical, and technological problems. This paper aims to show that the history of noise is an exciting story filled with drama and worth telling.
Keywords: Boltzmann equation; Brownian motion; Einstein theorem; Langevin equation; Weiner process; Matched filter; Noise history; Quantum noise; Shot noise; Stochastic differential equation; Thermal noise